Gamisoyo-San Ameliorates Neuroinflammation in the Spinal Cord of hSOD1G93A Transgenic Mice - MuDan Cai; Eun Jin Yang (Mediators of Inflammation)
Amyotrophic lateral sclerosis (ALS), a progressive disorder, causes motor neuron degeneration and neuromuscular synapse denervation. Because this is a complex disease, there are no effective drugs for the treatment of patients with ALS. For example, riluzole is used in many countries but has many side effects and only increases the lifespan of patients by approximately 2-3 months. Therefore, patients with ALS often turn to complementary and alternative medicine, such as acupuncture, homeopathy, and herbal medicine, with the hope and belief of recovery, despite the lack of definite evidence on the efficacy of these methods. Gamisoyo-San (GSS), a herbal medicine known to improve health, has been used for stress-related neuropsychological disorders, including anorexia, in Asian countries, such as China, Korea, and Japan. To evaluate the effects of GSS on the spinal cord, we investigated the expression of neuroinflammatory and metabolic proteins in symptomatic hSOD1G93A mice. We observed that GSS reduces the expression of glial markers, including those for microglia and astrocytes, and prevents neuronal loss. Moreover, we found that GSS inhibits the expression of proteins related to Toll-like receptor 4 signaling and oxidative stress, known to cause neuroinflammation. Notably, GSS also regulates metabolism in the spinal cord of transgenic mice. These results suggest that GSS could be used for improving the immune system and increasing the life quality of patients with ALS.